Photoswitchable diarylethene‐based polyurethane film for photorewritable patterning and stable information storage. Issue 20 (15th January 2019) - Yu, Maolin; Wang, Hong; Li, Yuqi; Zhang, Peisheng; Chen, Shu; Zeng, Rongjin; Gao, Yong; Chen, Jian
ABSTRACT: Photoswitchable polymeric materials are promising candidates for rewritable patterning and optical information storage. However, traditional solid photoswitchable polymers are generally hampered by a low fatigue resistance and slow photoresponse. To overcome these two key deficiencies, in this study, we examined a simple synthetic strategy for producing photoswitchable polyurethane films via the covalent attachment of an excellent photochromic diarylethene. The as‐prepared diarylethene‐based polyurethane (DTE–PU) film showed rapidly reversible isomerization and splendid photoreversibility (>20 times). Additionally, the as‐prepared DTE–PU film in the closed form possessed outstanding thermal irreversibility and long‐term optical stability. Photowritten patterns on the DTE–PU film remained steady for more than 2 weeks. These eminent properties made the DTE–PU film a promising candidate for multifarious applications, including rewritable patterning and stable optical information storage. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47466. Abstract : A photoswitchable diarylethene‐based crosslinked polyurethane film (DTE–PU) with good mechanical properties and excellent photoswitchable natures was prepared. Moreover, DTE–PU film in the close‐ring form has good thermal irreversibility and long‐term optical stability. The eminent properties imply the great potential in rewritable patterning and stable optical information storage.